Review of Blood Pressure Control in Vulnerable Older Adults: The Role of Frailty and Sarcopenia - Kunaal S. Sarnaik; Saeid Mirzai (Journal of Vascular Diseases)
The aging of the global population over recent decades has resulted in an increased prevalence of hypertension in older adults. Hypertension develops with increasing age primarily due to a disastrous feedback loop of increased arterial stiffness and maladaptive hemodynamics; this is compounded by age-related changes in physiology. The risk of adverse hypertension-related outcomes concurrently increases with age, and optimal blood pressure (BP) control in older adults thus becomes increasingly important each year. The results of several randomized clinical trials (RCTs) evaluating antihypertension strategies in older adults have concluded that the potential benefits of intensive BP management outweigh the risks of harm. However, the exclusion of frail, multimorbid, and institutionalized individuals limits the generalizability of such findings to the broader population of older patients with hypertension. Secondary analyses and external studies have continued to support intensive BP control strategies in older adults with frailty or sarcopenia. Therefore, based on available evidence, clinicians should continue practicing intensive BP control strategies in the older population, yet careful consideration of functional status, life expectancy, medication side effects, polypharmacy, and multimorbidity must take place to avoid unnecessary harm. Strategies must then be tailored to accommodate modifiers such as frailty and sarcopenia in older adults with hypertension. Knowledge gaps underscore the need for future studies evaluating BP management in older adults that incorporate greater proportions of multimorbid and institutionalized individuals with frailty, assess personalization of treatment, and identify subgroups in which optimal BP levels exist or the permissibility of higher BP levels is safer than BP reduction.